The patterns of in vitro cell-death and inflammatory cytokines induced by distinct BCG vaccine strains are differentially induced in human mononuclear cells. Issue 1 (2nd January 2018) - Ponte, C.; Hacker, M.; Moraes, M.; Castello-Branco, L.; Silva, F.; Antas, P.
ABSTRACT: Tuberculosis (TB) remains among the world's leading cause of mortality. For its control, studies of TB vaccines are needed. Since live-attenuated Mycobacterium bovis bacillus Calmette-Guérin (BCG) is the only TB vaccine currently in use, studies on the protective role of BCG are required. In this study, we analyzed host cells purified directly from whole blood of human immunodeficiency virus (HIV)-negative volunteers, comprising adult healthy donors (HD) and neonates (umbilical cord bloods, UCB), with the aim to directly compare in vitro immune responses with distinct BCG strains in human mononuclear cells. The Moreau, Pasteur, and Danish BCG strains were used to infect mononuclear cells in vitro for 48 h; bacilli viability and cell-death were subsequently detected by flow cytometry. In addition, cell culture supernatants were used in cytokine detection assays. Overall, the Moreau BCG strain induced higher levels of apoptosis than the Pasteur and Danish BCG strains in both the HD and UCB groups (p-value < 0.05), and a human monocytic cell-line mirrored those cell-death patterns after BCG infection. The Moreau BCG strain, exclusively, induced Th1 cytokines at the highest levels in cells from adults (p-value < 0.05) when compared with both Pasteur and Danish BCG strains, whereas TGF-β1 levels were reduced significantly (p-value < 0.01) in the HD group when cells were infected with the Moreau BCG vaccine. As expected, eight out of 22 pro-inflammatory cytokines were secreted at significant levels (p-value < 0.05) above the baseline rates in all BCG-infected cell cultures, in the HD group only. When analyzing these results, we excluded confounding factors related to storage and viability of the BCG strains used. These findings suggest that Moreau BCG is a more potent immunostimulating agent than the Pasteur and Danish BCG strains. Clinical trials will be needed to confirm these findings.